PENGINTEGRASIAN MATERI ENERGI BIOMASSA KE DALAM MATERI USAHA, ENERGI, MOMENTUM DAN IMPULS PADA PEMBELAJARAN HEURISTIC PROBLEM SOLVING - Riska Erfina Irsyad; Ahmad Fauzi; Hamdi Rifai (PILLAR OF PHYSICS EDUCATION, 2015)
One causes of low Physics learning outcomes is the lack of ability in creative thinking. It can solve by integrated biomass energy matterial and equipped with steps of heuristic problem solving learning. Integration of biomassa energy matterial expected to form energy efficient character to students. The purposes of these research are investigate the effects and contributed of integrated biomassa energy material to Physics learning outcomes. This research is Quasi Eksperiment Research with population were all of class XI MIA SMAN 12 Padang listed at 2014/2015 year academy. Results of research show the average of Physisc learning outomes are 82,62 and 74,90 at cognitive competence, 84,60 and 80,50 at affective competence, 87,80 and 85,10 at psikomotor competence. By using t analiys, tcount>ttable so alternatif hipotesis is accepted. From corelation analysis, the contributed of integrated biomass energy material is 66,8% to cognitive competence, 56,4% to affective competence and 67,1% to psikomotor comptence. The conclussions of these researh is there are significant effect and contribution of integrated biomass energy material to work, energy, momentum and impuls material in heuristiv problem solving learning